Implementation Of Autonomous Maintenance On Maintenance Of Three-Phase Slip Ring Induction Motor Used In Rubber Internal Motor Mixer - farhan mahaputra rahman; sentot wahjoe goeritno (Liaison Journal of Engineering, 2022)
The autonomous maintenance strategy involves the use of proactive maintenance techniques, to identify potential issues along with root causes within the motor. The maintenance strategy includes the development of degrees of maintenance actions to be done in the form of a schedule for routine maintenance tasks, such as cleaning, lubrication, and inspection, as well as the implementation of corrective maintenance procedures to address any identified issues. The effectiveness of the implemented strategies is evaluated through performance monitoring from prior and after the implementation of autonomous maintenance. Overall, the results of this study demonstrate the importance of implementing effective maintenance strategies for the reliable operation of three-phase slip ring induction motors in rubber internal mixers. By implementing these strategies, it is possible to prolong the lifespan of the motor and ensure the smooth operation of the mixer. Keywords: Three-Phase Induction Slip Ring Motor (3p-SR-IM), Rubber Internal Mixer (RIM), Autonomous Maintenance (AM), Maintenance Strategy, Proactive Maintenance